Structural, luminescence and Judd-Ofelt analysis to study the influence of post-annealing treatment on the AIN:Tb thin films prepared by radiofrequency magnetron sputtering - Tucto Salinas, Karem Yoli (2016)
This thesis investigates the effects of the annealing treatments on the spontaneous emission, radiative lifetime, composition and structure of terbium doped aluminum nitride films deposited on silicon substrates by radio frequency magnetron sputtering. The purpose of this thesis is to determine the Judd-Ofelt intensity parameters from the emission spectrum, in order to calculate the radiative lifetime, branching ratios and spontaneous emission probability. The optimal annealing temperature for the emission of terbium doped aluminum nitride is investigated. The annealing treatment was performed in the temperature range starting from 500 up to 1000°C. Two annealing techniques were investigated: rapid thermal processing and a rather slower quartz tube furnace. Furthermore, two heating approaches were applied: direct heating at 500, 750, 900 and 1000 °C, and multistep heating of 500-750°C, 750-900°C and 900-1000°C. The film was then characterized to determine which conditions resulted in the highest emission of Tb. The film characterization includes the use of X-ray diffraction to study the film’s crystal orientation, Energy dispersive X-ray spectroscopy to determine the film composition, Scanning electron microscopy and Reflection high-energy electron diffraction to resolve the surface morphology and structure of the film respectively. The luminescent intensity and the radiative lifetime were analyzed using cathodoluminescence measurement and Judd-Ofelt analysis. This work shows that the activation of the Tb ions to enhance the emitted cathodoluminescence intensity depends on the structure of the film and the oxygen concentration. The best annealing temperature to produce the highest emitted light intensity in this set of experiments were the single-step heating at 750°C using rapid thermal processing.